1999
DOI: 10.1097/00005768-199901000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Daily primary school physical education: effects on physical activity during adult life

Abstract: Our results strongly suggest that daily physical education at the primary school level has had a significant long-term positive effect on the exercise habits on women, despite similar perceived barriers, attitudes, and intention to exercise in the two groups. The program has also had a significant health effect in men, substantially reducing the risk of becoming a regular smoker. Because the program was not specifically designed to promote health, we hypothesize that a health-oriented physical education progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 19 publications
6
57
1
12
Order By: Relevance
“…If these levels of physical activity could be sustained, then multicolored playgrounds could make a valuable contribution to the achievement of health-related physical activity recommendations for young people. This would allow children to gain short-and long-term health benefits, and to maintain physically active lifestyles into adulthood (Trudeau et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…If these levels of physical activity could be sustained, then multicolored playgrounds could make a valuable contribution to the achievement of health-related physical activity recommendations for young people. This would allow children to gain short-and long-term health benefits, and to maintain physically active lifestyles into adulthood (Trudeau et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…School plays a vital role in promoting PA and shaping health behaviours to carry into adulthood; specifically PE is a good predictor of tracking PA from adolescence into adulthood (Trudeau, Laurencelle, Tremblay, Rajic, & Shephard, 1999). …”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with a very similar study, [26] but in contrast to other long-term follow-up studies in which reported leisure-time physical activity was still increased three to 20 years after the intervention. [27][28][29][30] It is possible that the validity of these studies which were based on activity assessments by questionnaires may have been hampered by factors such as social desirability and reporting or selection bias as these few programs did not measure or show persistent effects on aerobic fitness. [31,32] The lack of significant physical activity results in our study might reflect insufficient power due to a considerable dropout and non-compliance to wear the accelerometer, even in the children that attended the follow-up assessment.…”
Section: Discussionmentioning
confidence: 99%